Investigation on the formation of C54-TiSi2 used as contact metallization in ULSI application - Zhang, Lin (2008)
Titanium silicide has been widely adopted as a contact material for gate, source and drain of semiconductor devices in the industry for several generations. Its applicability to sub-quarter-micron technologies, however, has been questioned due to difficulties of obtaining low sheet resistance on small geometries.